Effect of Oral Riboflavin and Direct-sun UV-A on Tumor Necrosis Factor Alpha (TNF-α) Concentrations in Tears of Mild-Moderate Keratoconus Patients: Doi: 10.36351/pjo.v40i1.1690 - Aulia, Reza; Suhardjo Pawiroranu; Agni, Angela Nurini; Indra Tri Mahayana (Pakistan Journal of Ophthalmology, 2023)
Purpose: To determine the role of intra-silicon oil methotrexate injection to prevent Proliferative Vitreoretinopathy. Study Design: Quasi experimental Study. Place and Duration: Ophthalmology department of Sahiwal Teaching Hospital, Sahiwal from February 2022 to August 2022. Methods: Study included patients of either gender, older than 19 years with rhegmatogenous retinal detachment with Proliferative vitreoretinopathy (PVR) grade B or less. There were two groups and each group had fifty-one patients. All patients underwent pars plana vitrectomy and silicon oil tamponade. Group 1 was control group. Group 2 had intravitreal injections of methotrexate 500mg at the end of surgery. We repeated the injections at 1st, 2nd, and 4th week postoperatively. Results: There were 56 (54.9%) male and 46 (45.1%) female patients. Postoperatively visual acuity improved in thirty cases (58.82%) in group 1 and in forty-two cases (82.35%) in group 2. Postoperatively PVR developed in 11 (21.57%) patients in group 1 while in group 2 no patient had PVR. Recurrent Retinal detachment occurred in 9 (19.61%) patients in group 1 and 3 (5.88%) patients in group 2. Chi square test demonstrated statistically significant difference in the frequency of development of PVR and re-detachment of retina between two groups, p<0.05. Conclusion: Methotrexate is an effective adjuvant used in Pars plana Vitrectomy for rhegmatogenous retinal detachment repair. It prevents Proliferative vitreoretinopathy resulting in better surgical and functional outcome.